2011
DOI: 10.1007/s12011-010-8952-2
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Zinc Levels in Patients with Rheumatoid Arthritis

Abstract: The aim of the study was to evaluate zinc levels in three biological compartments (serum, erythrocytes and hair) in patients with rheumatoid arthritis (RA) as compared to healthy individuals. Zinc levels in serum, erythrocytes and hair (in 74 patients with RA and 30 healthy individuals) were assessed by atomic absorption spectroscopy. The mean hair zinc content was significantly lower in RA patients as compared to healthy individuals (p < 0.001). Moreover, a positive correlation was observed in the RA patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…These results suggest ZnONP has a chondrocprotective role. Previously, it was reported that serum Zn levels are found to be substantially decreased in rheumatoid arthritis (RA) 20,53 and that the reduced level of serum Zn in RA is associated with immune inflammatory processes. 54,55 In all hypoxia cases, up-regulation of HIF-1A gene expression [ Fig.…”
Section: Gene Expressionmentioning
confidence: 99%
“…These results suggest ZnONP has a chondrocprotective role. Previously, it was reported that serum Zn levels are found to be substantially decreased in rheumatoid arthritis (RA) 20,53 and that the reduced level of serum Zn in RA is associated with immune inflammatory processes. 54,55 In all hypoxia cases, up-regulation of HIF-1A gene expression [ Fig.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Ali et al (2019) have reported the niclosamide supplementation exert anti-rheumatoid activity in collagen-induced arthritis in rat model. Higher levels of copper and ceruloplasmin (Amancio et al 2003) and uric acid (Choe and Kim 2015) and a lower level of zinc were noted in rats with RA (Mierzecki et al 2011), possibly due to an elevated level of IL-1 (Nemeth et al 2002). Wang et al (2019) have reported that the curcumin attenuates collagen-induced rat arthritis through apoptotic and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…As zinc is considered anti-inflammatory with studies showing negative correlation between zinc and levels of IL-1 and TNF-. Mierzecki et al, 2011 18 have reported nonsignificant but higher levels of zinc in serum of RA patients. Though zinc levels should have been lower considering the role of proinflammatory cytokines as IL-1 and TNF- which inhibit albumin synthesis in liver and lower their zinc-binding capacity, which should in turn reduce the plasma zinc levels.…”
Section: Discussion:-mentioning
confidence: 99%
“…In recent studies RA seems to have derangement of mineral content like Mg, Zn, Cu and P. Their optimum concentration is required for normal functioning of the body. However alterations in level of these trace minerals as Mg 17 , Zn 18 and Cu (Copper) have been implicated in pathogenesis of RA as they are the co-factor of important enzymes involved in collagen and bone metabolism, the antioxidant defense system 19 and the immune system 20 . The development and progression of RA was suggested due to marginal deficiencies of Zn and Cu based on their ISSN: 2320-5407 Int.…”
mentioning
confidence: 99%